PROGRAM KEMITRAAN MASYARAKAT: Pelatihan Pembuatan Pakan Ikan Nila (Pelet) untuk Kelompok Bokape Fish Farm di Desa Bontokaddopepe, Takalar - Mukhlishah, Nurul; Mahi , Faizah; Nurdin, Nani Harlinda; Amri, Andi (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The Community Partnership Program (PKM) activity was carried out with the aim of providing counseling on the use of local raw materials to support independent feed needs for the Bokape Fish Farm tilapia farming group in Bontokaddopepe Village, North Galesong District, Takalar Regency. The problem faced by partners is the high price of tilapia feed sold on the market, while the need for tilapia feed must still be met in order to obtain maximum tilapia farming results. So that alternative solutions are needed to be able to create their own fish feed by utilizing available local materials, including corn. The method used is the Community Development approach method where the community plays an important role in the activities carried out. The results of this PKM activity show that 100% of partner group members agree that the training and practice that have been carried out can contribute to the growth of more optimal tilapia farming and provide new knowledge and independence in tilapia feed production for the future.